782. Clostridioides difficile environmental contamination in hospitalized patients with diarrhea: a pilot study. (31st December 2020) - Warren, Bobby G; Turner, Nicholas A; Addison, Rachel; Nelson, Alicia; Marden, Samantha; Gamez, Isabella; Smith, Becky A; Polage, Christopher R; Weber, David J; Weber, David J; Rutala, William; Sickbert-Bennett, Emily; et al.
Abstract: Background: The relative contribution of Clostridioides difficile colonization or infection in contamination of the hospital environment is poorly understood. Methods: We performed a prospective cohort study of patients with diarrhea who were tested for C. difficile infection via PCR and enzyme immunoassay (EIA) to compare C. difficile environmental contamination by test result. Patients were stratified into one of three cohorts: PCR -, PCR + /EIA + or PCR + /EIA - . Environmental microbiological samples were taken within 24 hours of C. difficile cultures and again for two successive days for a total of three days. Patients were excluded if they had C. difficile infection in the past 6-weeks. Microbiological samples of surfaces were obtained with pre-moistened cellulose sponges from three locations (bathroom, adjacent to bed, and care areas) and processed using the stomacher technique. Ribotyping was completed on a subset of stool and environmental samples to measure concordance of isolates. CFU and recovery rates between arms were compared with a global ANOVA followed by pairwise comparisons using a Bonferroni adjustment. Results: We enrolled 41 patients between November 2019 and March 2020. 7 patients were PCR + /EIA +, 8 were PCR + /EIA - and 26 were PCR - (Table 1). A total of 347 individual and 116 room samples were obtained. PCR + /EIA + patient rooms had a higher average room burden (435.6 CFU (95%CI: 178.0-694.0)) compared to PCR + /EIA - (83.5 ( - 9.1-175.0), p< 0.01) and PCR - rooms (17.1 (1.2-33.0), p< 0.01); PCR + /EIA - and PCR - rooms were similar (p=0.83). PCR + /EIA + patient rooms had a higher recovery rate (61%) compared to PCR + /EIA - (36%, p=0.64), although not statistically significant, and PCR - rooms (16%, p< 0.01); PCR + /EIA - had a similar recovery rate to PCR - rooms (p=0.14) (Table 2). Of the rooms with both patient and environmental isolates, 79% of patient isolates had a concordant isolate recovered in the environment. Table 1 Table 2 Conclusion: The amount of environmental contamination of PCR + /EIA + patients was higher than both PCR + /EIA - and PCR - patients, however, the recovery rate of PCR + /EIA + patients was similar to PCR + /EIA - patients. Subsequent larger trials are needed to expand on this pilot data to determine the difference, if any, between environmental contamination levels of these patient populations. Disclosures: David J. Weber, MD, MPH, PDI (Consultant)